Resource Management in the Petrochemical Industry - Stadtherr, Mark A.; Rudd, Dale F. (Management Science, 1978)
The petrochemical industry is a system of chemical processes that convert petroleum and natural gas into chemicals from which plastics, elastomers, and other synthetic materials can be made. As petroleum and natural gas supplies dwindle, this industry must look elsewhere for its raw materials. A linear-programming model of the industry is described, in which the objective is the efficient use of feedstocks. Four feedstock alternatives are evaluated with this model; the results of these studies are analyzed with respect to changes in the optimal process technology resulting from changes in feedstock availability. The model solutions also indicate the net change in feedstock requirement for the industry, per unit increase in demand for each product. This “feedstock efficiency index” indicates areas of incentive for developing new process technology; these areas are different for different feedstock alternatives. Analysis such as this should provide government planners with information for long-range planning and resource management.